Influence of Solvent Composition on the Performance of Spray-Dried Co-Amorphous Formulations - Jaya Mishra; Thomas Rades; Korbinian Löbmann; Holger Grohganz (MDPI AG, 2018)
Ball-milling is usually used to prepare co-amorphous drug-amino acid (AA) mixtures. In this study, co-amorphous drug-AA mixtures were produced using spray-drying, a scalable industrially preferred preparation method. The influence of the solvent type and solvent composition was investigated. Mixtures of indomethacin (IND) and each of the three AAs arginine, histidine, and lysine were ball-milled and spray-dried at a 1:1 molar ratio, respectively. Spray-drying was performed at different solvent ratios in (a) ethanol and water mixtures and (b) acetone and water mixtures. Different ratios of these solvents were chosen to study the effect of solvent mixtures on co-amorphous formulation. Residual crystallinity, thermal properties, salt/partial salt formation, and powder dissolution profiles of the IND-AA mixtures were investigated and compared to pure crystalline and amorphous IND. It was found that using spray-drying as a preparation method, all IND-AA mixtures could be successfully converted into the respective co-amorphous forms, irrespective of the type of solvent used, but depending on the solvent mixture ratios. Both ball-milled and spray-dried co-amorphous samples showed an enhanced dissolution rate and maintained supersaturation compared to the crystalline and amorphous IND itself. The spray-dried samples resulting in co-amorphous samples were stable for at least seven months of storage.